THE EFFECT OF COMBINATION OF LEG EXERCISE AND FOOT THERAPY USING TENNIS BALL ON THE FOOT SENSITIVITY OF PATIENTS WITH DIABETES MELLITUS IN THE WORKING AREA OF PUSKESMAS SAWAH LEBAR BENGKULU CITY IN 2023 - Widia Lestari; Adelina Damayanti; Mardiani Mardiani; Sahran Sahran; Erni Buston (Proceeding B-ICON, 2023)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia. The high prevalence of diabetes causes a risk of peripheral neuropathy, 90% of DM sufferers have neuropathy and 50% have peripheral neuropathy. With more than 10 million people living with diabetes, Indonesia has a prevalence rate of 6.2%. The prevalence of DM in the Bengkulu City area is 2,369 people and based on data obtained at the Sawah Lebar Community Health Center in Bengkulu City in 2021 there are 296 people. The purpose was to determine whether there was an effect of a combination of leg exercises and foot therapy using a tennis ball on the sensitivity of the feet of people with diabetes mellitus. This type of research uses a quasi-experimental design technique using a pre-post test design with a control group. With a research sample of 40 respondents who were divided into 2 groups. The intervention group was given a combination of leg exercises and foot therapy using a tennis ball, while the control group was given ROM measures which were carried out 3 times within 1 week. Analysis using the Wilcoxon test ? <0.05. to see if there is a difference in the average sensitivity of the feet before and after the intervention is given. Then the Mann Whitney U Test was carried out with ? <0.05 to assess whether there was a difference in the average sensitivity of the feet after. The results showed that the average sensitivity of the feet after the combined intervention of leg exercises and foot therapy using a tennis ball was 9.05 with a p value of 0.000 <0.05, which means that there was an effect of increasing foot sensitivity after being given the intervention.